Product Label Design Training for MSMEs Producing Typical Lempuk Fish in Grati, Pasuruan Regency: Pelatihan Desain Label Produk UMKM Pengolah Ikan Lempuk Khas Grati Kabupaten Pasuruan - Puspitarini*, Erri Wahyu; Maukar, Anastasia Lidya; Haryanto, Kurniawan Wahyu; Arifianto, Teguh; Rahardiyanto, Panca (Universitas Lancang Kuning, 2024)
The Lempuk fish, scientifically known as Gobiopterus spp., is a species of fish that exclusively inhabits the Ranu Grati lake in Pasuruan Regency. It is notable for its high protein content. PKK women utilise the processed Lempuk fish to create crispy lempuk. The issue at hand is that a significant number of these women lack the necessary expertise to create their own packaging label designs. Despite the items' excellent nutritious potential and pleasing taste. The objective of this Community Service is to enhance partners' proficiency in the design of processed products using Grati Typical Lempuk Fish. The design training method involves collaborative practice sessions followed by autonomous application utilising the Canva software. Design talents have shown a 60% boost. Partners utilise Canva to enhance their package labels, indicating their successful efforts in changing their product packaging design to transform them into processed lempuk items with a greater market value.